Tongue-operated assistive technology with access to common smartphone applications via Bluetooth link - Jeonghee Kim; Hangue Park; Ghovanloo, M. (2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2012)
Tongue Drive System (TDS) is a wireless and wearable assistive technology (AT) that enables people with severe disabilities to control their computers, wheelchairs, and electronic gadgets using their tongue motion. We developed the TDS to control smartphone's (iPhone/iPod Touch) built-in and downloadable apps with a customized Bluetooth mouse module by emulating finger taps on the touchscreen. The TDS-iPhone Bluetooth mouse interface was evaluated by four able-bodied subjects to complete a scenario consisting of seven tasks, which were randomly ordered by using touch on the iPhone screen with index finger, a computer mouse on iPhone, and TDS-iPhone Bluetooth mouse interface with tongue motion. Preliminary results show that the average completion times of a scenario with touch, mouse, and TDS are 165.6 ± 14.50 s, 186.1 ± 15.37 s, and 651.6 ± 113.4 s, respectively, showing that the TDS is 84.37% and 81.16% slower than touch and mouse for speed of typing with negligible errors. Overall, considering the limited number of commands and unfamiliarity of the subjects with the TDS, we achieved acceptable results for hands-free functionality.